Self-driven in situ facile synthesis of CuO/Cu2O for enhanced catalytic reduction of 4-nitrophenol by acetic acid. (2nd August 2022) - Zhu, Ting; He, Qian; Wang, Ziwei; Zhang, Juan; Li, Hanke; Fu, Hongquan; Liao, Fang
Abstract : A series of CuO, Cu2 O and CuO/Cu2 O catalyst structures with different morphologies are synthesized in situ by controlling the anionic species of the copper salts in the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP). Abstract : A series of CuO, Cu2 O and CuO/Cu2 O catalyst structures with different morphologies are synthesized in situ by controlling the anionic species of the copper salts in the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP). The prepared CuO/Cu2 O-rAc is used to catalytically reduce 4-NP. It shows that CuO/Cu2 O-rAc prepared using Cu(Ac)2 ·H2 O as the copper source exhibits a higher k of 0.2019 min −1 and a k m of 0.2019 min −1 μg −1 . The catalytic reduction property is in accordance with the CH3 COOH content of CuO/Cu2 O-rAc . The obtained CuO and Cu2 O can form a heterojunction structure, improving the electron-transfer rate for enhancing the adsorption of 4-NP and the desorption of 4-AP. Moreover, a key factor that affects the catalytic efficiency of CuO/Cu2 O-rAc is the pH, which affects NaBH4 to form H2 . This production strategy is highly efficient and can be used to fabricate other similar catalytic hydrogenation reactions.